PUSAT INFORMASI GEOPARK MERATUS DI BANJARBARU - Muhammad Ar-Rafiqul A la; Bani Noor Muchamad (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2026)
The Meratus Geopark possesses significant potential in geological, ecological, and cultural aspects that must be managed sustainably through conservation, education, and local economic development. However, there is currently no information center capable of presenting these potentials comprehensively and immersively to local, national, and international visitors. The main challenges in designing the Meratus Geopark Information Center include issues of accessibility, infrastructure availability, and the effectiveness of information delivery to visitors. To address these challenges, the interpretative approach and the immersive information concept are applied in the design process. The interpretative approach is employed to translate the geological, ecological, and cultural values of the Meratus region into meaningful architectural elements, allowing the building to function as a medium of communication between humans and their environment. Meanwhile, the immersive information concept supports the creation of an interactive and in-depth educational experience through spatial organization, lighting design, and visual technology. Through the implementation of these two approaches, the Meratus Geopark Information Center is expected to serve as an educational and conservation facility that effectively communicates information while also functioning as a cultural and sustainable tourism promotion center, contributing to environmental awareness and local economic growth.